“The Old Foods Are the New Foods!”: Erosion and Revitalization of Indigenous Food Systems in Northwestern North America - Joseph, Leigh; Turner, Nancy J. (Frontiers in Sustainable Food Systems, 2020)
The global “nutrition transition” has had an immense impact on Indigenous Peoples of Northwestern North America. From an original diet comprised of mostly local plant and animal foods, including salmon, game, diverse plants, seaweed and other marine foods, many Indigenous people are now eating mostly imported, refined marketed foods that are generally less healthy, and many are at risk of diet-related diseases such as type 2 diabetes. Nevertheless, Indigenous people have always valued their ancestral foods, and over the last few decades there have been many initiatives throughout the region to restore and revitalize these original foods, and to re-learn Indigenous methods of processing and harvesting them. In this paper we describe the original Indigenous food systems in the study region, and the methods used to sustain and promote the ancestral food species and habitats. We then discuss the impacts of colonization, and describe recent and ongoing Resilience and Resurgence in relation to ancestral foods and food practices, including firsthand experiences with renewing food traditions. These initiatives are often connected with language revitalization and cultural resurgence programs. Led by Indigenous communities, they are undertaken with support of academic, government and other partners. In all, they have resulted in stronger, more vibrant cultures and generally healthier communities.